Strategi Adaptasi untuk Berbicara Bahasa Sunda sebagai Komunikasi Antarbudaya Di Universitas Padjadjaran - Muhamad Rafi Said Pratama; Dirgantara , Pradipta (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
Intercultural communication often occurs in student life. The diverse campus consists of multi-ethnic students. One of them is the existence of Padjadjaran University which is a campus thick with its motherhood and is an educational destination for students outside Bandung. The purpose of this study was to find out how non-Sundanese students adapted and used what strategies to speak Sundanese with Sundanese students at Padjadjaran University. The theory used for this study is the accommodation communication toeri. this research method is qualitative. This study used Communication Accommodation Theory (CAT). The subjects of this study were three students from Padjadjaran University and the object of the study was what strategy they used to speak Sundanese as intercultural communication. The data collection technique of this study used semi-structured in-depth interviews. The results of this study showed that the three students used convergence strategies in intercultural communication. This strategy emphasizes speakers to follow the local language because they feel they have something in common with the Sundanese identity, are willing to use the Sundanese language and learn to use their accents and tones, and have the same motivation, namely using the Sundanese language to adapt to the local culture.